Level of interleukin-35 in patients with idiopathic membranous nephropathy and its predictive value for remission time - Zhang, Na; Dai, Haoran; Dong, Xuan; Liu, Wenbin; Jiang, Hanxue; Zhao, Qihan; Gao, Yu; Feng, Zhendong; Dong, Zhaocheng; Hu, Yuehong; Huang, Guangrui; Rui, Hongliang; et al. (Frontiers in Immunology, 2022)
Objective As a member of interleukin-12 family, interleukin-35 (IL-35) plays an important regulatory role in immune response. The relationship between IL-35 and idiopathic membranous nephropathy (IMN) is still unclear, and the purpose of this study is to clarify the relationship between IL-35 and disease activity and remission of IMN. Methods This study was a single-center, retrospective study in which all patients were diagnosed with IMN by renal biopsy or aPLA2R titer and treated with Mahuang Fuzi and Shenzhuo Decoction (MFSD). A follow-up was conducted with the endpoint of clinical complete or partial remission (PR+CR). Levels of serum IL-35 were measured and its relationship with IMN remission were analyzed. The regulatory T cell (Treg) and inducible IL-35 producing Tregs (iTR35) in peripheral blood of IMN patients were detected by flow cytometry. Results A total of 76 IMN patients (age 51.95±13.29) were followed-up for 18 (12, 24) months. The level of serum IL-35 in all patients increased after treatment, but the degree of increase in remission group was significantly higher than that in no remission (NR) group (117.6% vs 83.7%, P<0.01). The baseline IL-35 level in remission group was higher than that in NR group (174.87 vs.151.87 pg/ml, P=0.016). Cox regression analysis showed that baseline IL-35 level was a independent risk factor for IMN remission (HR 1.081, 95%CI 1.048-1.116, P<0.001). Patients with baseline IL-35 lower than the lower quartile (< 145.49 pg/ml) had an average remission time twice as long as those with baseline IL-35 higher than the upper quartile (> 203.05 pg/ml) (12mon vs. 24mon, P<0.01). The baseline IL-35 can predict the remission time of IMN patients with either aPLA2R positive (AUC=0.673) or negative (AUC=0.745). Analysis of 18 patients with IMN showed that IL-35 level had a higher correlation with iTR35, but not Treg (r=0.613, P<0.05). Conclusions The level of IL-35 in patients with IMN showed an increasing trend with the progress of treatment, and the baseline IL-35 could predict the remission time of IMN patients, including those patients with negative aPLA2R. The level of IL-35 is related to the number of iTR35 cells.